Ordinal Logistic Regression with an Application to Health Service Quality in Raden Mattaher Jambi Hospital - Feri Tiona Pasaribu; Ainun Mardia; Corry Sormin (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
Health care is a treatment received by the community provided by health workers. The quality of health services will provide satisfaction to health services. Service actions that affect the value of satisfaction are availability and completeness of facilities, physical evidence of administration, reliability of officers, responsiveness of officers, guarantees received by patients and families of patients, and empathy felt by patients. This level of satisfaction assessment is in the form of an ordinal scale that is not satisfied, less satisfied, satisfied and very satisfied. The analysis used to determine the level of satisfaction is by ordinal logistic regression analysis. The sample used in this study is the patient or family of patients at Raden Mattaher Hospital. The stages of data analysis used are the validity and reliability test, parameter estimation, model feasibility test, parameter significance test and the best model selection. The results of the analysis obtained the best models and with factors that influence the level of quality of health services at Raden Mattaher Hospital, namely physical evidence, availability and completeness of facilities and responsiveness.